Effect of clean intermittent self-catheterization on urinary tract infection in subject with spinal cord injury - Rachmawati, Maria Regina; S, Suleiman; Wirawan, Rosiana P. (Universa Medicina, 2008)
Patients with spinal cord injury are often unable to empty their bladders sufficiently. If this condition is left untreated, urinary tract infection (UTI) is unavoidable, with potentially lethal consequences. The objective of this study was to evaluate the effect of clean intermittent self-catheterization (CIC) on urinary tract infection in subject with spinal cord injury. A randomized controlled design was conducted in subjects who lived at two dormitories were included in this study. They were randomized to clean intermittent self- catheterization or control group. All the subjects were followed for one months. Primary outcome measure was symptomatic urinary tract infection as diagnosed by, pyuria (leukocytes of 100,000 or more per high power field.). Twenty-six patients between 22 to 62 years with cervical spinal cord injuries and urine residue more than 50 cc were recruited. Of the 26 subjects, 18 (69.2%) developed urinary tract infection. The incidence rate of UTI in the CIC group was 5/13 (38.5%); significantly lower than the control group 11/13 (84.6%) (p=0.016). Clean intermittent self catheterization in patient with spinal cord injury decreased the risk of developing urinary tract infection.